Relationship between Serum Elabela Level and Hypertensive Nephropathy - Dogan, Yusuf; Onalan, Erhan; Cavli, Cundullah; Onalan, Ebru Etem; Yakar, Burkay; Donder, Emir (Coll Physicians & Surgeons Pakistan, 2021)
Objective: To determine the difference in serum Elabela level in hypertensive patients with and without nephropathy compared to the healthy control group. Study Desing: Cross-sectional descriptive study. Place and Duration of Study: Firat University Medical School, Elazig, Turkey between December 2018 and November 2020. Methodology: The cross-sectional descriptive study consisted of 37 patients with hypertensive nephropathy (group 3), 50 hypertensive patients without nephropathy (group 2), and 50 healthy controls (group 1).Hypertensive nephropathy was defined as serum creatinine >= 1.8 mg / dl or GFR <40 ml / minute. Biochemical parameters (Glucose, AST, ALT, urea, creatinine, lipid levels, hemogram, calcium, phosphorus, parathormone) and the levels of serum Elabela were evaluated and compared. Results: There was no significant difference in age (0.270) and gender (0.951) between groups. The median Elabela levels of the three groups were 40.3 ng/mL (22.5-54.6), 5.1 ng/mL (3.7-8.3), 9.2 ng/mL (6.1-23.1), respectively with a significant difference (p<0.001). Conclusion: The plasma levels of Elabela were lower in the case of hypertension, independent of nephropathy. However, this decrease is not specific for nephropathy and may be due to other accompanying chronic diseases.
Keywords: Hypertension; Hypertensive nephropathy; Elabela